Trends in Robotics and Computer Integrated Manufacturing - Dixit, Anil Kumar; Kumar, T. Vijaya; Joshi, Abhishek; Bedi, Harpreet Singh; Chakravarthi, M. Kalyan; Singh, Devesh Pratap (2022 5th International Conference on Contemporary Computing and Informatics (IC3I), 2022)
Today, all manufacturing businesses are expected to have the ability to produce high-quality goods with shorter lead times and the capacity to produce to a variety of customer specifications. Any industry's production capacity has increased exponentially as a result of the use of robots in manufacturing. To resolve the aforementioned problems and maintain a nation's revenue in the fiercely competitive international market, robotics and computer integrated manufacturing (CIM) technology are required. The main emphasis is placed on the robot's accuracy during milling operations, and its capacity to carry out the work with the required precision is assessed. The manipulator stiffness model is utilized to estimate failures in conformity caused by the baseline cutting force, which is the same for all robots under consideration, in order to calculate this performance metric. The feasibility of the suggested method was demonstrated in experimental research including the milling of circular notches using a robot for a variety of workgroup samples and locations. As cutting force increases, the circularity index raises as well, and it may be calculated by simple scaling. The study suggests a system that is focused on the industry and allows users to rate industrial robots according to their machining precision. Some industrial robots from the KUKA family that have been graded for various machining jobs are used to test the established methodology.